PENGGUNAAN MODEL PEMBELAJARAN WORD SQUARE DALAM MENINGKATKAN PEMAHAMAN KONSEP PEMBELAJARAN IPS - Aini nur arifa subarjah; Lili Dianah; Sudarmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aimed to examine the effectiveness of the Word Square learning model in improving students’ conceptual understanding in social studies. The study was conducted in two cycles involving observation, documentation, and tests to measure changes in students’ performance and learning engagement. Findings indicate that the implementation of the Word Square model significantly enhanced students’ ability to interpret, exemplify, classify, summarize, compare, and draw conclusions regarding key social studies concepts. Students became more active and involved during group discussions, task completion, and reflection, showing increased motivation and focus. Learning outcomes also improved, as seen in the rise of average scores and mastery percentages across cycles. The Word Square model provided a learning experience that was enjoyable, challenging, and interactive, supporting students’ conceptual development through linguistic and visual engagement. However, several challenges emerged, such as varied student literacy skills, limited time allocation, and the complexity of preparing Word Square grids. These issues can be addressed through better planning, technological integration, and task-level adjustments. Overall, the Word Square model proved effective in strengthening conceptual understanding in social studies and is recommended as an alternative learning strategy. Future research may explore its application across different grade levels, materials, or in combination with other learning models to expand its pedagogical impact.